Crossing Death Valley: Bringing Neurotechnology to Psychiatric Clinics in Alberta, Canada - MacMaster, Frank P.; Mitchell, Nick; Bichel, Allison; Bercov, Marni; Thompson, Gayle; Suen, Victoria; Strilchuk, Allison; Rittenbach, Katherine (Frontiers in Psychiatry, 2020)
Depression is a major public health problem, with a lifetime and 12-month prevalence estimated at 18% and 6% of adults. Depression is costly in terms of treatment and lost productivity and is the main burden of mental illness across the globe. Existing pharmacological and psychological treatments for depression result in clinically meaningful improvements in less than 60% of patients. An emerging treatment approach is non-invasive brain stimulation of depression-related brain targets through transcranial magnetic stimulation (TMS). In this perspective, we detail our efforts on bringing TMS to clinical populations in Alberta by utilizing a novel organizational structure that bridges the gap between academia and the health care system. The Addictions and Mental Health Strategic Clinical Network worked with stakeholders to (1) examine the evidence, (2) develop clinical tools for patient selection and protocol application, (3) create overall implementation and evaluation plans to aid in further scale and spread, and even (4) fund the purchase and deployment of devices. Through this work, five publicly supported clinics now exist in Alberta.